Characterisation of 2-HP-β-cyclodextrin-PLGA nanoparticle complexes for potential use as ocular drug delivery vehicles - Fan Li; Yuqin Wen; Yan Zhang; Kangyu Zheng; Junfeng Ban; Qingchun Xie; Yifeng Wen; Qing Liu; Fohua Chen; Zhenjie Mo; Lizhong Liu; Yanzhong Chen; et al. (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Aim 2-HP-β-cyclodextrin-PLGA nanoparticle complexes were prepared to enhance the aqueous humour delivery of Triamcinolone acetonide.Materials & methods Drug-loaded 2-HP-β-CD/PLGA nanoparticle complexes prepared by adapting a quasi-emulsion solvent evaporation technique. In vitro drug release, in vitro transcorneal permeation study, histopathological study and in vivo transcorneal penetration of PLGA nanoparticles and 2-HP-β-CD/PLGA nanoparticle complexes were evaluated. Results Particle size distributions of 2-HP-β-CD/PLGA nanoparticle complexes were 149.4 ± 3.7 nm and presented stable system. Corneal penetration studies revealed steady sustained drug release (First-order); 2-HP-β-CD/PLGA nanoparticle complexes increased ocular bioavailability by increasing dispersion in the tear film and improving drug release. Conclusion 2-HP-β-CD/PLGA nanoparticle complex formulation is a promising alternative to conventional eye drops.